EFFECTIVENESS, SAFETY, AND SIDE EFFECT OF DEPO PROGESTIN AND DEPO VIGESTRON CONTRACEPTION - Budi Santoso; Jimmy Yanuar Annas; Heriyadi Manan; Nizam Albadawi; Marina Marina; Maria Anggraeni; Leli Asih (Universitas Airlangga, 2017)
Introduction: Trends in contraceptive injections increased in the last two decades. Hormonal contraceptive injection is available in single or combination dose. However, the products are available more than 1 ml (more than recommendation of WHO). This study aims to determine the effectiveness, safety and side effects of the contraceptive injection Depo Progestin® 3 ml, Depo Vigestron® 3 ml and Depo Vigestron® 1 ml. Method: This study used randomized controlled clinical trial and open label. The research subject were 900 people in two center, Surabaya and Palembang. The samples were divided into 3 (three) groups, group Depo Progestin® vial 3 ml, group Depo Vigestron® vial 3 ml, and group Depo Vigestron® vial 1 ml. Each of consist 300 women using the "random permutation block". Analysis was performed 5 times, when an initial injection and a schedule of repeated injections in the 3rd, 6th, 9th and 12th month. The data analyzed include weight, blood pressure, menstrual pattern, and the complaints of the patients. Results: From the 900 only 862 valid samples. The results showed no signi fi cant difference between groups Depo Progestin® 3ml, Depo Vigestron® 3 ml and Depo Vigestron® 1 ml. The majority of respondents experienced an increase in weight, but still within normal limits, did not have increased blood pressure, increased menstrual blood volume, Pregnancy didn't occured to all respondents and found no abnormalities in cervical cytology. Conclusion: Contraceptive injection of Depo Progestin® 3 ml, Depo Vigestron® 3 ml dan Depo Vigestron® 1 ml, have used during 12 months can be concluded that those tree kind of contraception were efective, safe and had no side effect.